Intraspecific variability in heat resistance of fungal conidia. (June 2022) - van den Brule, Tom; Punt, Maarten; Seekles, Sjoerd J.; Segers, Frank J.J.; Houbraken, Jos; Hazeleger, Wilma C.; Ram, Arthur F.J.; Wösten, Han A.B.; Zwietering, Marcel H.; Dijksterhuis, Jan; den Besten, Heidy M.W.
Graphical abstract: Highlights: Heat resistance of A. niger, P. roqueforti and P. variotii was characterized. Experimental, biological and strain variabilities were quantified. Strain variability of the three fungal species was comparable. Degree of intraspecies variability was rather similar for bacterial and fungal species. Abstract: Microbial species are inherently variable, which is reflected in intraspecies genotypic and phenotypic differences. Strain-to-strain variation gives rise to variability in stress resistance and plays a crucial role in food safety and food quality. Here, strain variability in heat resistance of asexual spores (conidia) of the fungal species Aspergillus niger, Penicillium roqueforti and Paecilomyces variotii was quantified and compared to bacterial variability found in the literature. After heat treatment, a 5.4- to 8.6-fold difference in inactivation rate was found between individual strains within each species, while the strain variability of the three fungal species was not statistically different. We evaluated whether the degree of intraspecies variability is uniform, not only within the fungal kingdom, but also amongst different bacterial species. Comparison with three spore-forming bacteria and two non-spore-forming bacteria revealed that the variability of the different species was indeed in the same order of magnitude, which hints to a microbial signature of variation that exceeds kingdom boundaries.